High flow rate microreactors integrating in situ grown ZnO nanowires for photocatalytic degradation. Issue 3 (5th January 2022) - Martin, Nathan; Lacour, Vivien; Perrault, Cécile Mong-Tu; Roy, Emmanuel; Leprince-Wang, Yamin
Abstract : A high flow rate, low-pressure microfluidic photocatalytic microreactor was created and demonstrated here. Abstract : A high-volume, low-pressure microfluidic photocatalytic microreactor was created and demonstrated here. This high-flow rate microreactor, based on an innovative design developed by the start-up Eden Tech, was produced by a simple thermal pressing process, using Eden Tech's easy-to-use and environment-friendly thermoplastic polymer, Flexdym™. ZnO nanowires (ZnO NWs) were then synthesized in situ, using an environment-friendly, low-cost, two-step hydrothermal method. Varying the synthesis parameters (growth solution flow rate, time and temperature) allowed us to get an insight into the optimal synthesis conditions for photocatalytic purposes. The in situ grown nanowire morphology was characterized using scanning electron microscopy (SEM). The photocatalytic efficiency of the as-synthetized microreactors was tested by degrading continuous streams of water polluted with Acid Red 14 (AR14), a commonly used organic dye, under UV irradiation, followed by UV-visible spectrometry. We found that the best results are obtained with the following synthesis parameters: a 1 h growth time, a growth flow rate of 200 μL min −1 and a temperature of 80 °C. After 4 passes in the reactor, which is roughly equivalent to 40 seconds of UV light irradiation, the dye was degraded at 98%. Increasing the photocatalysis flow rate from 200 μL min −1 to 500 μL min −1 showed a small decrease in efficiency, but it is still encouraging for high-flow rate degradation.